Characterization of pantropic canine coronavirus from Brazil - Pinto, Luciane D. (Vet J, 2014)
Characterization of canine coronavirus (CCoV) strains currently in circulation is essential for understanding viral evolution. The aim of this study was to determine the presence of pantropic CCoV type IIa in tissue samples from five puppies that died in Southern Brazil as a result of severe gastroenteritis. Reverse-transcriptase PCR was used to generate amplicons for sequence analysis. Phylogenetic analysis of the CCoV-IIa strains indicated that they were similar to those found in other countries, suggesting a common ancestor of these Brazilian isolates. This is the first report of pantropic CCoV-II in puppies from Latin America and our findings highlight that CCoV should be included as a differential diagnosis when dogs present with clinical signs and lesions typically seen with canine parvovirus infection.